Intensive Supervision for High-Risk Offenders in 14 Sites in the United States, 1987-1990 - Petersilia, Joan ([Verlag nicht ermittelbar], 1999)
In 1986, the Bureau of Justice Assistance (BJA) funded a demonstration project of intensive supervision programs (ISPs), alternatives to control sanctions that involve community sanctions and emphasize stringent conditions and close monitoring of convicted offenders. The primary intent of the demonstration project was to determine the effects of participation in an ISP program on the subsequent behavior of offenders and to test the feasibility of the ISP's stated objectives: (1) to reduce recidivism by providing a seemingly cost-effective alternative to imprisonment, and (2) to provide an intermediate punishment between incarceration and regular probation that allows the punishment to fit the crime. Fourteen sites in nine states participated in the project and each of the selected sites was funded for 18 to 24 months. Individual agencies in each site tailored their ISP programs to their local needs, resources, and contexts, developed their own eligibility criteria, and determined whether probationers met those criteria. While the individual ISP projects differed, each site was required to follow identical procedures regarding random assignment, data collection, and overall program evaluation. Data collection instruments that differed in the amount of drug-related questions asked were used for the six- and twelve-month reviews. The "non-drug" data collection instrument, used in Contra Costa, Ventura, and Los Angeles counties, CA, Marion County, OR, and Milwaukee, WI, gathered drug data only on the number of monthly drug and alcohol tests given to offenders. The "drug" data collection instrument was distributed in Atlanta, Macon, and Waycross, GA, Seattle, WA, Santa Fe, NM, Des Moines, IA, and Winchester, VA. Variables regarding drug use included the number of drug tests ordered, the number of drug tests taken, and the number of positives for alcohol, cocaine, heroin, uppers, downers, quaaludes, LSD/hallucinogens, PCP, marijuana/hashish, and "other". The drug questions on the instrument used in Dallas and Houston, TX, were the same as those asked at the drug sites. Once a site determined that an offender was eligible for inclusion, RAND staff randomly assigned the offender to either the experimental ISP program (prison diversion, enhanced probation, or enhanced parole) or to a control sanction (prison, routine probation, or parole). Assignment periods began in January 1987 and some sites continued to accept cases through January 1990. Each offender was followed for a period of one year, beginning on the day of assignment to the experimental or control program. The six-month and twelve-month review data contain identical variables: the current status of the offender (prison, ISP, or terminated), record of each arrest and/or technical violation, its disposition, and sentence or sanction. Information was also recorded for each month during the follow-up regarding face-to-face contacts, phone and collateral contacts, monitoring and record checks, community service hours, days on electronic surveillance (if applicable), contacts between client and community sponsor, number and type of counseling sessions and training, days in paid employment and earnings, number of drug and alcohol tests taken, and amount of restitution, fines, court costs, and probation fees paid. Background variables include sex, race, age at assignment, prior criminal history, drug use and treatment history, type of current offense, sentence characteristics, conditions imposed, and various items relating to risk of recidivism and need for treatment. For the two Texas sites, information on each arrest and/or technical violation, its disposition, and sentence or sanction was recorded in separate recidivism files (Parts 10 and 17). Dates were converted by RAND to time-lapse variables for the public release files that comprise this data collection.